(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Pantawid Pamilyang Pilipino Program (4Ps), implemented by the Department of Social Welfare and Development (DSWD), is a national government human development program that invests in the health and education of poor households, particularly children aged 0-18 years old. President Rodrigo Roa Duterte signed Republic Act No.11310, or An Act Institutionalizing the Pantawid Pamilyang Pilipino Program (4Ps), on April 17, 2019, making Pantawid Pamilya the government’s national poverty reduction policy. The use of computer and communication technology that are integrated to support administrative activities in an office setting is commonly thought of as digitalization. Automated office systems are well- organized methods of managing in the workplace. The implementation of office digitalization should be monitored and evaluated to identify any issues and to make necessary improvements. By following these recommendations, and organizations can effectively implement office digitalization to improve the productivity level of administrative personnel in the office environment, leading to increased efficiency, cost- effectiveness, and overall workplace performance. The study concludes that office digitalization has the potential to significantly enhance the productivity level of administrative personnel. However, it is important for organizations to provide adequate training and support for administrative personnel to ensure that they are able to effectively utilize digital tools to increase productivity. Overall, the findings of this study contribute to our understanding of the impact of office digitalization on the productivity level of administrative personnel and have important implications for organizations seeking to improve efficiency and productivity in their administrative functions.